KEPEMIMPINAN DEMOKRATIS KEPALA SEKOLAH DAN KEDISIPLINAN SISWA - Muhammad Ripin Ikhwandi; Triana Rosalina Noor,; Reski Amalia,; Hutiya (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
Education is essentially a cultural process to improve human dignity and at thesame time prepare the next generation for its role in the future. In this educational endeavor,the school education pathway is a neatly organized, planned, tiered and continuous path.Besides that, school education is a forum for achieving national education goals. Therefore,so that education can run well and in accordance with the expected goals, it is necessary topay attention to various things that determine the direction of achieving this goal, one of thedeterminants of achieving the goal of education in the school environment is the principal.From the description of the background, several problems can be formulated as follows: 1)What is the democratic leadership style of the Sidoarjo Antartika Vocational School Principal?: 2) How is the discipline of students in the Sidoarjo Antartika Vocational School (SMK)?: 3)How far is the influence the principal's democratic leadership style towards the discipline ofstudents in the Antartika Vocational School (SMK) Sidoarjo ?; 4) How far is the influence ofthe principal's democratic leadership style on the discipline of students at the AntartikaVocational School (SMK) in Sidoarjo ?.The purpose of this study are: a. To explain the democratic leadership style of the AntartikaVocational School Principal (SMK) in Sidoarjo .; b. To describe the discipline of the SidoarjoAntartika Vocational School (SMK) students: c. To prove the influence of the principal'sdemocratic leadership style on the discipline of the Sidoarjo Antartika Vocational School(SMK) students; d. Measuring how far the principal's democratic leadership style influencesthe discipline of the Sidoarjo Antartika Vocational School (SMK) students.The approaches and methods used in this study are quantitative research, because researchprocesses data using statistics, so the data must be in the form of quantitative data, in theform of numbers. The results of this study are as follows: 1. Style of Democratic Leadership inthe head of the Antartika Vocational School in Sidoarjo at a good level, 2. The discipline ofSidoarjo Antartika Vocational students is at a good level. 3 Styles of Democratic Leadershipin the Sidoarjo Antartika Vocational School have a positive influence on student discipline. 4.From the results of the interpretation indicate that between X and Y variables there is acorrelation is being